Pengetahuan Dan Sikap Ibu Hamil Sebelum Dan Setelah Diberikan Pendidikan Kesehatan Dalam Pencegahan Ketuban Pecah Dini (KPD) - Reka Anggie Estina; Endang Susilowati; Endang Surani (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2023)
Premature rupture of membranes (PROM) is a tear in the amniotic skin that occurs before the time of delivery, either in the latent phase, namely opening 1-3 in birthing women or at gestational age entering the second or third trimester. The incidence of KPD is influenced by the lack of knowledge and attitudes of pregnant women regarding the danger signs of pregnancy. The purpose of this study was to find out the differences in knowledge and attitudes of pregnant women before and after being given health education using leaflets in an effort to prevent premature rupture of membranes at the Puri Asih Public Hospital, Salatiga. Method of the research is quantitative research with a one group pretest posttest design approach, the sampling technique used is consecutive sampling and the data collection method uses a questionnaire. The statistical test used is the Wilcoxon signed rank test. The results of the study showed that there were significant differences in the knowledge and attitudes of pregnant women before and after being given health education through leaflets in the prevention of KPD with a p value of 0.000.